An Overview of the Pathogenesis of Immune-mediated Skin Injury. (June 2016) - Danilenko, Dimitry M.
The skin has a relatively limited range of responses to injury regardless of the specific mechanism underlying the insult. When the skin's barrier function is disrupted, it mounts an inflammatory and proliferative response in an effort to restore this essential function. The epidermal keratinocyte is central to the initiation of the skin's response, triggering an immunologic cascade that leads to the stereotypic morphologic responses that we encounter as pathologists. Drug-induced immune-mediated cutaneous injuries or "drug eruptions" are relatively common, sometimes with overlapping mechanisms, and it is often possible to classify these based on the classical hypersensitivity-type reactions. A specific type of immune-mediated skin injury is psoriasis. The pathogenesis of psoriasis is multifactorial but involves the interaction of environmental factors with a genetic predisposition. The initial stimulus triggering the development of psoriatic lesions involves activation of epidermal keratinocytes, with subsequent amplification driven by cross talk between the adaptive and innate immune systems. Several cytokines produced by Th17 T helper cells have recently been shown to be important in the pathogenesis of psoriasis, namely, interleukin-23 (IL-23) and IL-17, due to demonstrated clinical efficacy of cytokine blockade; and IL-22, based on its effects in both in vitro and in vivo models.